Keberadaan bakteri patogen pada sampel pangan jajanan anak sekolah dasar di Pulau Sapeken, Sumenep, Jawa Timur - Dayanara, Ivani; Kawuri, Retno; Yulihastuti, Dwi Ariani (Jurnal Biologi Udayana; Vol 23 No 2 (2019): JURNAL BIOLOGI UDAYANA, 2019)
School children snacks are food that is found and routinely consumed by children in the school environment. Good and healthy food must be free from hazardous and toxic materials, such as microbial contamination, chemicals and other materials. The consumed food must meet the microbial contamination requirements based on SNI (Standar Nasional Indonesia) safety testing. Pathogenic bacteria still a serious problem in various countries including Indonesia, since they are capable of causing foodborne diseases. Sapeken Island is located in Sapeken Village, Sapeken District, Sumenep Regency, East Java Province. The purpose of the study was to determine the presence of pathogenic bacteria in samples of snacks for school children on Sapeken Island. The method used was the Most Probable Number (MPN) for Escherichia coli, Test Number of Bacillus sp., Test Number of Staphyllococcus sp., Identification of Salmonella, and Total Plate Count (TPC). The test results obtained in the MPN of Escherichia coli included SD M (9.9 ± 3.8) MPN / g, SD 5 (8.68 ± 2.73) MPN / g, SD IT (5.08 ± 0.66) MPN / g, and SD 4 (4.26 ± 2.44) MPN / g exceed the SNI limit. JURNAL BIOLOGI UDAYANA 23(2): 60-71 P ISSN: 1410-5292 E ISSN: 2599-2856 61 The results of JPT E. coli in snack empek-empek at SD I and SD 2, and JPT E. coli ojek in all elementary schools is <3 MPN / g. The results of the empek-empek and ojek samples in all elementary schools for all tests with the parameter number Bacillus sp. is <1 x 103, the number of Staphylococcus sp. is <1 x 102, Salmonella identification is negative, TPC is <1 x 105 CFU / g. The conclusion of the study is snack for school children (empek-empek) and ojek on Sapeken Island does not contain contamination of pathogenic bacteria Escherichia coli, Bacillus sp., Staphylococcus sp., Salmonella identification, and TPC, except for the JPT E. coli test on empek empek in SD M, SD 5, SD IT and SD 4 that exceed SNI limits.